An efficient multi-scale approach for viscoelastic analysis of woven composites under bending. (15th July 2022) - Le, An; Nimbalkar, Sanjay; Zobeiry, Navid; Malek, Sardar
Abstract: This paper investigates the bending response of cured and uncured viscoelastic composite laminates at different loading rates to gain a better understanding of the fibre waviness effect on wrinkling evolution during the forming process of advanced composites. This is accomplished by the implementation of a three-dimensional (3D) multi-scale modelling framework that incorporates analyses at different scales (micro-, meso- and macro-scale). For micro- and meso-scale simulations, analytical models proposed in the literature are investigated for estimating the material properties, while a differential form (DF) of viscoelasticity implemented as a UMAT is employed for structural level (macro-scale) simulations. Combining analytical equations at smaller scales with the DF form of viscoelasticity at macro-scale, a rapid method for estimating the effect of various parameters on wrinkle formation is developed. The numerical model is validated by comparing the bending behaviour of thin viscoelastic composites with experimental data reported in the literature. The influence of various parameters including fibre stiffness, ply anisotropy, resin properties, and loading rates on the bending behaviour of composites are analysed. The agreement between the numerical predictions and the experimental data highlights the potential of the proposed multi-scale modelling framework to predict the behaviour of viscoelastic composite with a variety of yarn architectures efficiently. Further experimental investigations into the viscoelastic characteristics of woven composites at the micro- and meso-scale are advised to ascertain the limitations and validity range of the predictions.